A family of metal-organic frameworks exhibiting size-selective catalysis with encapsulated noble-metal nanoparticles - Zhang, Weina (2014)
The encapsulation of noble-metal nanoparticles (NPs) in metal-organic frameworks (MOFs) with carboxylic acid ligands, the most extensive branch of the MOF family, gives NP/MOF composites that exhibit excellent shape-selective catalytic performance in olefin hydrogenation, aqueous reaction in the reduction of 4-nitrophenol, and faster molecular diffusion in CO oxidation. The strategy of using functionalized cavities of MOFs as hosts for different metal NPs looks promising for the development of high-performance heterogeneous catalysts.